Performance Analysis and Design of Fibre Gratings for Sensing Applications - Nidhi (My University, 2014)
The role of optical technologies for non-contact type of measurements in the field of instrumentation and sensing is revolutionary. The exceptional sensitivity of fiber towards external perturbation has made research world extremely benefited. This property is explored to construct a large variety of instruments and sensors. This thesis also deals with the performance analysis and design of fiber gratings for sensing applications. Long Period Gratings (LPGs) are proposed as simple yet versatile optical fiber sensors. In case of LPG, periodic modulation of refractive index within core region is written in such a way that light propagating in the core can interact with cladding and outside thereby yielding an output spectrum that includes changes due to all external parameters to which the fiber may be subjected to. The phase matching condition causes light from the fundamental mode to couple with discrete forward-propagating cladding modes. These cladding modes attenuate rapidly on propagation and result in loss bands at discrete wavelengths in the grating transmission spectrum. One of the aims of this work has been to develop an analytical model to predict the location of resonance bands as function of grating periods as well as core and cladding refractive indices. The transmission characteristics of uniform LPGs are simulated theoretically by using coupled-mode theory. Studies undertaken in the thesis include review of number of LPG fabrication methods and understanding the mechanism of photosensitivity in germanosilicate fibers using different reported models. The fabrication of these gratings has been done using TeraXian grating writing station. In this work, uniform LPGs are fabricated by using a line-narrowed KrF excimer laser adopting point by point method. The fibers used in experiments are photosensitive optical fibers (Boron co-doped) and gratings can be written directly into these fibers without hydrogenation. In the thesis it is experimentally demonstrated that the high refractive index overlay increases the refractive index sensitivity of LPG refractive index sensor. The utilization of Indium Tin Oxide (ITO) as coating material enhances refractive index sensitivity of LPG due to the phenomena of rearrangement of cladding modes. This thesis gives an insight about the scope of LPG for relative humidity (RH) measurement applications. For realization of LPG based humidity sensors, unique feature of LPG i.e. its susceptibility to perturbations in the surrounding medium is investigated. It has been previously reported that coating the cladding of LPGs with thin layer of specific coating materials brings about sensing capability for certain target application. Taking account of this finding, LPG has been coated with a hygroscopic mixture of Cobalt chloride doped Gelatine by dip coating technique. Refractive index measurements and thin film characterisation have been performed by Refractometry, FE-SEM and NSOM imaging respectively. The coated LPG has been experimentally tested for its response to relative humidity levels varying from 35% to 90%. The designed sensor gives an output response of 0.18 nm/%RH. The ITO and CoCl2/gelatine coated LPG as humidity sensor is also demonstrated very first time. The sensor measured RH variation efficiently in the range of 40 % to 95 %RH with sensitivity of 0.12 nm/%RH. The thesis also highlights the investigative study of Fiber Bragg Grating (FBG) written in multi-mode fibers (MMF). The fabrication is done by phase mask technique using the static mode of grating writing station. The gratings are characterized by taking different concentration of glycerol solutions. The effect of temperature and strain is studied theoretically using software Optigrating 4.2.2. Also, FBG as a current sensor is demonstrated successfully by using two configurations: with housing and without housing. The minimum and maximum values of measured current are 0.05 Amp and 1 Amp for without housing and it is 1 Amp and 4 Amp with housing setup. The designed sensor has accuracy 0.05 Amp and repeatability 95%. This sensor is different from available current sensors in terms of its new and simple design, low cost and ability to withstand harsh environment. Thus research work presented in this thesis combines refractive index sensitivity enhancement of LPG by using simple dip coated Indium tin Oxide overlay on it. Further sensor/coating attachment method to develop an RH sensor for informative evaluation of the humidity effect using gelatin and cobalt chloride combination on LPG surface.All the issues addressed in the work contribute to implement a simple and economical index of refraction and moisture measurement system. These sensors offer numerous advantages in corrosion monitoring, chemical & food processing and biochemical sensing. The investigative study of FBG in MMF is very useful for developing low cost sensing systems. Most of the research findings of the thesis have been published in various international referred journals as per list at pages (207-208).
Ph.D, ECED, Thesis
Keywords: Fiber grating; humiditiy; Long period grating; Fiber bragg gratings; electronics and communication